(untitled) (Experimental biology, 2009)
Regional peculiarities of external respiratory function in males and females living on the territory of Northern Kazakhstan were investigated. It was found that a number of external respiratory parameters differ from the due values. At the same time the volumetric - temporal parameters, characterizing patency of bronchial tree, were 30-46% lower than the due value. Lagging of actual parameters of external respiration behind the due values in young women of Northern Kazakhstan was caused by the complex influence of climatic-ecological factors and low motion activity.